2022
DOI: 10.1021/acs.est.1c04152
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Impacts of PM2.5 Constituents on Adult Mortality in China

Abstract: Limited evidence exists for long-term effects of PM 2.5 constituents on mortality. Hence, we aimed to assess associations between all-cause mortality and long-term exposure to PM 2.5 constituents in China. We designed a nationwide cohort study of 30524 adults from 162 prefectural areas across mainland China with follow-ups through years 2010−2017. Cox proportional hazards models with time-varying exposures were employed to quantify associations between all-cause mortality and long-term exposure to PM 2.5 and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“… 30 In addition, animal studies have reported that exposure to NO 3 – may result in lung inflammatory cell infiltration, alveoli collapse, and thickening of the small airway wall. 31 We also discovered a strong link between NH 4 + and mortality, and the strength of the observed association was consistent with previous studies 23 , 32 that the effect of NH 4 + ranked top among the contributing factors. However, it is unclear whether the observed associations are due to their intrinsic toxicity or because they are associated with other combustion-emitted culprit pollutants.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“… 30 In addition, animal studies have reported that exposure to NO 3 – may result in lung inflammatory cell infiltration, alveoli collapse, and thickening of the small airway wall. 31 We also discovered a strong link between NH 4 + and mortality, and the strength of the observed association was consistent with previous studies 23 , 32 that the effect of NH 4 + ranked top among the contributing factors. However, it is unclear whether the observed associations are due to their intrinsic toxicity or because they are associated with other combustion-emitted culprit pollutants.…”
Section: Discussionsupporting
confidence: 91%
“…We observed linear relationships with BC (Exposure II), SO 4 2– , and NH 4 + , with no indication of a threshold for either outcome, and the previously published studies in Southeastern U.S. and China also reported similar linear association for BC (Exposure II), NO 3 – , and SO 4 2– . 20 , 23 We observed nonlinear “bell-shaped” C – R relationships between exposure to BC (Exposure I), OM, and DUST and mortality, indicating that the relationships are increasing steeply at low to moderate exposure levels and leveled off at high exposure levels. There have been many theories proposed to explain the reasons causing a nonlinear C – R relationship, including preferential avoidance based on symptoms, decreased inhalation, and errors in estimating pollution exposure levels at elevated concentrations.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Prior research has indicated that PM 2.5 can pose risks to a variety of health outcomes such as mortality, lung cancer, and respiratory and cardiovascular diseases. Additionally, in recent years, its detrimental impact on reproductive health has garnered widespread attention. …”
Section: Introductionmentioning
confidence: 99%